Properties of calcium phosphates ceramic composites derived from natural materials - N. Lertcumfu (2018)
© 2016 Elsevier Ltd and Techna Group S.r.l. In this study, ceramics containing mixed phases of hydroxyapatite/beta-tricalcium phosphate (HA/β-TCP) were fabricated by a solid-state reaction technique. The HA powder was synthesized from cockle shells while the β-TCP powder was synthesized from egg shells. Pure HA and β-TCP fine powders were successfully obtained. The HA and β-TCP were mixed and subjected to a thermal treatment up to 1100 °C. To form the mixed phase ceramics, the resulting powders were sintered at 1350 °C. Effects of HA concentration on the properties of the studied ceramic were investigated. X-ray diffraction analysis revealed that all samples presented multiphase of calcium phosphate compounds. Average grain size of the ceramics decreased with the HA additive content. The 75 wt% HA ceramic showed the maximum hardness value (5.5 GPa) which is high when compared with many calcium phosphate ceramics. In vitro bioactivity test indicated that apatite forming increased with the HA additive content. To increase antibacterial activity, selected ceramics were coated with AgNO3. Antibacterial test suggested that an Ag compound coating on the ceramics could improve the antibacterial ability of the studied ceramics. In addition, the antibacterial ability for the Ag coated ceramics depended on the porosity of the ceramics.